2008
DOI: 10.1128/aac.01370-07
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of SPK-843, a Novel Polyene Antifungal, in a Murine Model of Systemic Cryptococcosis

Abstract: SPK-843, a new polyene antifungal, possessed efficacy in a murine model of systemic infection caused byCryptococcus neoformans. The administration of 4.0 mg/kg SPK-843 led to better survival prolongation and fungal reduction than those observed with the administration of 0.7 mg/kg amphotericin B and 80 mg/kg fluconazole (P < 0.001), without histopathological renal changes.Cryptococcus neoformans is fungus that is an important cause of morbidity and mortality in immunocompromised patients. Central nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…The inability of amphotericin to reduce the fungal burden in the organs of partially complement deficient AJCr mice after 3 days of treatment was explained by the follow-up study with a trend towards reduction of CFUs in brains and lungs manifesting itself only on the 14 th day of treatment. These observations are in concert with literature showing that even in intact robust mice as CD-1 or Balb/c amphotericin as deoxycholate was also only able to produce 1–1.5 log reduction in CFUs and all mice died around day 24 (13, 14). It is also in concert with the data from clinical studies showing that a short course of amphotericin does not sterilize cerebrospinal fluid or blood and that the rate of sterilization correlates with survival (15).…”
Section: Discussionsupporting
confidence: 88%
“…The inability of amphotericin to reduce the fungal burden in the organs of partially complement deficient AJCr mice after 3 days of treatment was explained by the follow-up study with a trend towards reduction of CFUs in brains and lungs manifesting itself only on the 14 th day of treatment. These observations are in concert with literature showing that even in intact robust mice as CD-1 or Balb/c amphotericin as deoxycholate was also only able to produce 1–1.5 log reduction in CFUs and all mice died around day 24 (13, 14). It is also in concert with the data from clinical studies showing that a short course of amphotericin does not sterilize cerebrospinal fluid or blood and that the rate of sterilization correlates with survival (15).…”
Section: Discussionsupporting
confidence: 88%
“…The explanation of the inability of amphotericin to decrease the fungal burden in the organs of partially complement deficient AJ/Cr mice 3 days post treatment was provided by the subsequent amphotericin study showing a trend towards decrease in CFUs in brains and lungs which manifested itself only on day 14 th of treatment with amphotericin B. Our results are in concordance with the published data showing that amphotericin was able to produce only a 1–1.5 log reduction in CFUs in immunocompetent mice such as CD-1 and Balb/c and all mice succumbed to CN infection around day 24 [8, 9]. Our results also agree with the clinical reports which showed that a short course of amphotericin was not able to sterilize cerebrospinal fluid or blood of patients and which also correlated the rate of sterilization with the patients survival [10].…”
Section: Fungal Infectionssupporting
confidence: 90%
“…The inability of amphotericin to reduce the fungal burden in the organs of partially complement deficient AJCr mice after 3 days of treatment was explained by the follow-up study with a trend towards reduction of CFUs in brains and lungs manifesting itself only on the 14th day of treatment ( Figure 5(f) ). These observations are in concert with literature showing that even in intact robust mice as CD-1 or Balb/c amphotericin as deoxycholate was also only able to produce 1–1.5 log reduction in CFUs and all mice died around day 24 [ 27 , 28 ]. It is also in concert with the data from clinical studies showing that a short course of amphotericin does not sterilize cerebrospinal fluid or blood, and that the rate of sterilization correlates with survival [ 29 ].…”
Section: Comparison Of Rit Of Cn With Standard Antifungal Treatmensupporting
confidence: 86%